Evaluation of health-related quality of life among patients with chronic obstructive pulmonary disease at District Headquarter Hospital haripur, Pakistan - Mehwish Fayaz; Shahbaz Ahmad Zakki; Ijaz Ul Haq; Muhammad Afzal; Mudassar Latif; Ehtisham Altaf (Clinical Epidemiology and Global Health)
Background & objectives: Chronic obstructive pulmonary disease (COPD) is a notable worldwide public health issue and a major cause of morbidity and mortality in Pakistan. The objective of this study was to assess the health-related Quality of Life (HRQoL) among patients diagnosed with COPD and to explore the determinants that impact it. Methods: This cross-sectional study comprised 400 individuals diagnosed with COPD who were aged 30–75. The St. George's Respiratory Questionnaire (SGRQ), which is specific to COPD, was employed to assess the patient's quality of life. The overall score of all three domains, namely activity, impact, and symptoms, was calculated. The chi-square test was used to find out the association between the SGRQ scores and the respondent's characteristics. Results: The mean score of SGRS was 59.04 ± 1.03, indicating worse health. About 60 % (n = 240) of the participants had phlegm most of the day. Additionally, most of them 62 % (248) suffered from cough most days a week, with a p-value of 0.010, and the shortness of breath (p < 0.001) was significantly associated with the total SGRQ score. Shortness of breath (p-value <0.001) and cough (p-value 0.010) were significantly associated with the total SGQR score. Conclusion: The impairment of quality of life is a notable issue among patients diagnosed with COPD, and it tends to worsen as the disease progresses in severity. The need of the hour is to promote awareness about COPD in the community and sensitize healthcare professionals towards its effects on HRQoL.